2007
DOI: 10.1007/s11205-007-9160-0
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Well-being Among Young People in Transition to Adulthood

Abstract: Life satisfaction, Early adulthood, Subjective well-being, Intergenerational life satisfaction,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 31 publications
(28 reference statements)
2
18
0
2
Order By: Relevance
“…This result is also consistent with the findings of past research that the socio-economic status of young people is associated with their life satisfaction (Trzcinski & Holst, 2008;Saha et al, 2014).…”
Section: The Effect Of Individual Family and Societal Factors On Lifsupporting
confidence: 93%
See 1 more Smart Citation
“…This result is also consistent with the findings of past research that the socio-economic status of young people is associated with their life satisfaction (Trzcinski & Holst, 2008;Saha et al, 2014).…”
Section: The Effect Of Individual Family and Societal Factors On Lifsupporting
confidence: 93%
“…Education achievement is also considered to be an important factor in young people's lives and some research showed that young people with a higher education were more satisfied than others (Trzcinski & Holst, 2008;Proctor et al, 2009;Chappel et al, 2014). In this study, respondents' education was measured by considering the highest level of education achieved.…”
Section: %) These Figures Also Indicate That Australian and Secondmentioning
confidence: 99%
“…Given the short-term longitudinal data base, the study was able to examine not only whether parenting behavior influences adolescent wellbeing, but also whether differences in levels of adolescent well-being influence parenting behavior. Given the unique nature of relationships with parents during the time of adolescence versus adulthood, such research may yield implications for public policies related to the well-being of young people during the transition to adulthood (Trzcinski and Holst 2008).…”
mentioning
confidence: 99%
“…Tal vez esto es debido a que aunque ambos progenitores son importantes para hijos e hijas, la influencia materna tiende a ser algo superior a la paterna (Hair et al, 2008;Rodrigo et al, 2004). Por ejemplo, es más perjudicial para el ajuste adolescente que las madres muestren un estilo indiferente a que lo hagan los padres (Simons y Conger, 2007), quizá porque para el bienestar adolescente son centrales el afecto materno (Cheng y Furnham, 2004), la comunicación con la madre (Morrow, 2004) y la calidad de la relación con la madre (Trzcinski y Holst, 2008). Tampoco hay que olvidar en esta consideración que la mayor dedicación e influencia de la madre frente al padre responde mejor a las expectativas que nuestra cultura tiene puestas en ambos (Menéndez y Hidalgo, 2003;Menéndez, Hidalgo, Jiménez y Moreno, 2011).…”
Section: Discussionunclassified